Strategi Pengembangan UMKM di Masa Pemulihan Pasca Pandemi Covid-19 (Studi Kasus CV. Kreasi Pangan Kita) - Pangestu, Fajar Puja; Utomo, Sugeng Hadi (Universitas Batanghari Jambi, 2024)
MSMEs have a very important role in the Indonesian economic system. The important role of MSMEs in the lives of Indonesian people includes reducing unemployment, stabilizing the economy of the entire region, and having an influence on the national foreign exchange market. Currently, the development of MSMEs in Indonesia continues to grow rapidly. However, in the midst of the development of MSMEs, Covid-19 emerged which hampered the development of all sectors, including MSMEs. In this regard, the aim of this research is to determine the effectiveness of MSME development strategies after the Covid-19 pandemic, where in this research samples were taken from CV. Our Food Creations. The research method used is qualitative type with descriptive analysis. The approach used is a case study approach. Then, data collection techniques for primary data are through observation, interviews and documentation carried out directly, while for secondary data through the MSME website. The data testing process uses the IFAS (Internal Factor Analysis Strategic) and EFAS (External Factor Analysis Strategic) analysis methods which are combined or matched with the creation of SWOT diagrams and tables. The results obtained are that there are 18 alternative growth-oriented development strategies, so that CV. Kreasi Pangan Kita has a good opportunity to develop its business after the Covid-19 pandemic.